'Not at the diagnosis point': Dealing with contradiction in autism assessment teams. (January 2021) - Hayes, Jennie; McCabe, Rose; Ford, Tamsin; Parker, Daisy; Russell, Ginny
Abstract: Social science literature has documented how the concept of diagnosis can be seen as an interactive process, imbued with uncertainty and contradiction, which undermines a straightforward notion of diagnosis as a way to identify underlying biological problems that cause disease. We contribute to this body of work by examining the process of resolving contradiction in autism diagnosis for adults and adolescents. Autism is a useful case study as diagnosis can be a complex and protracted process due to the heterogeneity of symptoms and the necessity to interpret behaviours that may be ambiguous. We audio-recorded and transcribed 18 specialist clinical assessment meetings in four teams in England, covering 88 cases in two adult, one child and one adolescent (14+) setting. We undertook a qualitative analysis of discursive processes and narrative case-building structure utilised by clinicians to counteract contradiction.We identified a three-part interactional pattern which allows clinicians to forward evidence for and against a diagnosis, facilitates their collaborative decision-making process and enables them to build a plausible narrative which accounts for the diagnostic decision. Pragmatism was found to operate as a strategy to help assign diagnosis within a condition which, diagnostically, is permeated by uncertainty and contradiction. Resolution of contradiction from different aspects of the assessment serves to create a narratively-coherent, intelligible clinical entity that is autism. Highlights: Diagnosis of autism in adults and young people can be complex and contradictory. Discursive analysis examined how teams deliver a coherent diagnostic narrative. An interactional pattern in team decision-making helps to resolve contradiction. Considering social outcomes is used as a strategy to help assign diagnosis. This decision-making process contributes to how we understand autism.